Application of Lagrange Interpolation Method in Predicting the Number of HVS Orders in Printing - Triana, Dinie; Putri, Amelia; Faradhilah, Anatasia; Sitorus, Yolanda Angelina (Holistic Science, 2024)
The research entitled “Application of the Lagrange Interpolation Method in Predicting the Number of HVS Orders in Printing” aims to develop an accurate forecasting model for the number of HVS orders in the printing industry. In this study, the Lagrange interpolation method was chosen because it can provide estimates by considering limited historical data. The analyzed data ranges from January 2021 to November 2022 and is processed to build a forecasting model. The results showed that the interpolation model built was able to capture well the fluctuation pattern of the order quantity. Model evaluation is carried out using Mean Absolute Percentage Error, which reads <=10%, indicating high prediction accuracy. In addition, sensitivity analysis to data variations showed consistent results of the prediction, thus strengthening the validity of the method. These findings suggest that Lagrange interpolation is an effective tool in forecasting HVS demand, providing advantages in inventory management and production planning in printing houses.